2020
DOI: 10.1007/s00167-020-06102-5
|View full text |Cite|
|
Sign up to set email alerts
|

Intra-articular injections of platelet-rich plasma in symptomatic knee osteoarthritis: a consensus statement from French-speaking experts

Abstract: Purpose There has been much debate regarding the use of intra-articular injections of platelet-rich plasma (PRP) as symptomatic treatment for knee osteoarthritis. The objective of this consensus was to develop guidelines for PRP injections in knee osteoarthritis according to the French National Authority for Health recommendations. Methods Fifteen physicians from different French-speaking countries (10 rheumatologists, 4 specialists in rehabilitation and sports medicine and 1 radiologist) were selected for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 101 publications
(258 reference statements)
2
24
0
3
Order By: Relevance
“…The importance of neutrophils in PRP is unclear. Systematic reviews identified LP-PRP as the preferred PRP formulation to achieve effective treatment outcomes for joint OA [ 33 ]. However, Lana et al [ 34 ] opposed the use of LP-PRP in knee OA treatment, suggesting that particular leukocytes play an important role in the inflammatory process preceding tissue regeneration due to their release of both pro and anti-inflammatory molecules.…”
Section: Prp Terminology and Classificationmentioning
confidence: 99%
“…The importance of neutrophils in PRP is unclear. Systematic reviews identified LP-PRP as the preferred PRP formulation to achieve effective treatment outcomes for joint OA [ 33 ]. However, Lana et al [ 34 ] opposed the use of LP-PRP in knee OA treatment, suggesting that particular leukocytes play an important role in the inflammatory process preceding tissue regeneration due to their release of both pro and anti-inflammatory molecules.…”
Section: Prp Terminology and Classificationmentioning
confidence: 99%
“…The importance of neutrophils in PRP is unclear. Systematic reviews identified LP-PRP as the preferred PRP formulation to achieve effective treatment outcomes for joint OA (25). However, Lana et al (26) opposed the use of LP-PRP in knee OA treatment, suggesting that particular leukocytes play an important role in the inflammatory process preceding tissue regeneration due to their release of both pro and anti-inflammatory molecules.…”
Section: A-prfmentioning
confidence: 99%
“…A recent consensus 29 described the low to moderate knee OA as proper indication for PRP injections. A careful patient selection is recommended because severe radiographic changes appeared to be correlated to poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This was not confirmed for hyaluronic acid injections as no differences were found. It's well known that corticosteroids have a catabolic activity of PRP and Eymand et al 29 recommend a delay if steroids are injected before PRP. Nevertheless, Camurcu et al 36 demonstrated that single steroid injection followed by PRP 1 week later improve the clinical response in patients with low or moderate knee OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation